Performance of Mali's biosafety level 3 laboratory in the external quality assessment in preparedness of laboratory accreditation and support to clinical trials - N Coulibaly; B Kone; M Sanogo; A C G Togo; B Diarra; Y S Sarro; A B Cisse; O Kodio; G Coulibaly; M Kone; B Baya; M Maiga; et al. (International Journal of Mycobacteriology, 2020)
Background: The external quality assessment (EQA) or external quality control is an evaluation conducted by a certified external organization to inquire about the quality of the results provided by a laboratory. The primary role of EQA is to verify the accuracy of laboratory results. This is essential in research because research data should be published in international peer-reviewed journals, and laboratory results must be repeatable. In 2007, the University Clinical Research Center (UCRC's) biosafety level 3 (BSL-3) laboratory joined the EQA program with the College of American Pathologists in acid-fast staining and culture and identification of mycobacteria as per laboratory accreditation preparedness. Thus, after 11 years of participation, the goal of our study was to evaluate the performance of our laboratory during the different interlaboratory surveys. Methods: We conducted a descriptive retrospective study to evaluate the results of UCRC mycobacteriology laboratory from surveys conducted during 2007 and 2017. Results: Of the 22 evaluations, the laboratory had satisfactory (100% of concordance results) in 18 (81.8%) and good (80% of concordance results) in 4 (18.2%). Overall, the laboratory was above the commended/accepted limits of 75%. Conclusion: So far, UCRC's BSL-3 performed well during the first 11 years of survey participation, and efforts should be deployed to maintain this high quality in the preparedness for laboratory accreditation and support to clinical trials.